👤

1+2x{11+9x[8+(6+a)]:8-20}:4-5=5

Răspuns :

1+2*{11+9*[8+(6+a)]:8-20}:4-5=5
1+2*{11+9*[8+(6+a)]:8-20}:4=5+5
1+2*{11+9*[8+(6+a)]:8-20}:4=10
2*{11+9*[8+(6+a)]:8-20}:4=10-1
2*{11+9*[8+(6+a)]:8-20}:4=9
2*{11+9*[8+(6+a)]:8-20}=9*4
2*{11+9*[8+(6+a)]:8-20}=36
{11+9*[8+(6+a)]:8-20}=36:2
11+9*[8+(6+a)]:8-20=18

11+9*[8+(6+a)]:8=18+20
11+9*[8+(6+a)]:8=38
9*[8+(6+a)]:8=38-11
9*[8+(6+a)]:8=27
[8+(6+a)]:8=27:9

[8+(6+a)]:8=3
8+(6+a)=3*8
8+(6+a)=24
(6+a)=24-8
6+a=16
a=16-6
a=10
6+10=16





1+2x{11+9x[8+(6+a)]:8- 20}:4=5+5
1+2x{11+9x[8+(6+a)]:8- 20}:4=10
1+2x{11+9x[8+(6+a)]:8- 20}=4x10
1+2x{11+9x[8+(6+a)]:8- 20}=40
2x{11+9x[8+(6+a)]:8+20}=40-1
2x{11+9x[8+(6+a)]:8+20}=39
{11+9x[8+(6+a)]:8+20}=2x39
[11+9x8+(6+a):8+20]=78
[11+72+(6+a):8+20]=78
[83+(6+a):8+20]=78
(83+6+a:8+20)=78
89+a:8+20=78
89+a:8=78-20
89+a:8=58
a:8=89+58
a:8=31
a=31:8
a=...